Promoting a Multidimensional Literacy Framework through Texts and Tasks for EFL Reading Class - Luluk Iswati (LPPM Universitas Bumigora Mataram, 2022)
Generally, the teaching of reading for English as a foreign language (EFL) learner is only focused on developing learners’ English language competence. Little had been done to stimulate learners to develop Kucer’s (2014) multidimensional literacy that consists of four stages: linguistic, cognitive, sociocultural, and developmental. The teaching of reading should be aimed beyond the classroom context. It should not only evoke learners’ linguistic and cognitive ability, but should also elicit them to go further into sociocultural and developmental aspects. Thus, this study is aimed at proposing a multidimensional framework of literacy through texts and tasks so that they will be beneficial for learners’ actual use of literacy in their everyday life. This paper proposes a modified model of Kucer’s multidimensional literacy which is combined with principles in reading texts selection and reading tasks. The framework suggests that the degree of text difficulty and unfamiliarity should be gradually increased as well as the level of tasks challenge and variety.